(3eQBI GdCjGe hGdOQLs - (3eMeO eYQha, fLe GdOjfs
(3ChdgG (B:s
(3GdMeO ddg eHOY dchf Ydi NjQ eKGd hHYO ajbhd gPg QSGdI JJVef UaI EdI GNJQYJ CSdhHgG ai JGQjN jXgQ ef MSGH ESegG hgh eQBI GdCjGe hGdOQL s
(3BNQgG (B:s
(3hbSehG gPg GdafcGJ Ydi GdLGZGJ hGdcgaGJ aNU cd LGZ KeGfjI hLYdhG GHJOGA Gdjhe HdjdJg ef NGeS ef GdLGZ GdChd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B128 - (3U(B145s
(3HgG CTcGd hLOGhds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdHQjWGfi (B(7416) s
Keywords: (3Gdadcs